2003
DOI: 10.1007/s10038-003-0082-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of the GM2 gangliosidosis B variant

Abstract: To study the structural basis of the GM2 gangliosidosis B variant, we constructed the threedimensional structures of the human b-hexosaminidase a-subunit and the heterodimer of the a-and b-subunits, Hex A, by homology modeling. The a-subunit is composed of two domains, domains I and II. Nine mutant models due to specific missense mutations were constructed as well and compared with the wild type to determine structural defects. These nine mutations were divided into five groups according to structural defects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…In R499C, the cysteine residue might create an illegitimate disulfide bridge in the protein with a resultant disruption of the normal three-dimensional structure, causing a more severe clinical phenotype than in R499H (Akli et al, 1993). Our study of the structural analysis by molecular modeling software showed no drastic structural changes in a subunit polypeptides with R499C/H (Matsuzawa et al, 2003), which was consistent with the mild clinical phenotypes.…”
Section: Discussionsupporting
confidence: 72%
“…In R499C, the cysteine residue might create an illegitimate disulfide bridge in the protein with a resultant disruption of the normal three-dimensional structure, causing a more severe clinical phenotype than in R499H (Akli et al, 1993). Our study of the structural analysis by molecular modeling software showed no drastic structural changes in a subunit polypeptides with R499C/H (Matsuzawa et al, 2003), which was consistent with the mild clinical phenotypes.…”
Section: Discussionsupporting
confidence: 72%
“…The root-mean-square graduate value was set at 0.05 kcal/mol Å . Then, each mutant model was superimposed on the wild-type structure based on the Ca atoms by the least-square-mean fitting method (Kabsch 1976(Kabsch , 1978Sakuraba et al 2000Sakuraba et al , 2004Matsuzawa et al 2003Matsuzawa et al , 2005. We defined that the structure was influenced by an amino acid substitution when the position of an atom in a mutant differed from that in the wild type by more than the cutoff distance (0.15 Å ) based on the total RMSD, as described previously (Matsuzawa et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The R499H mutation causes loss of stabilization between domains I and II of the α-subunit without affecting the active site of the enzyme. 98 These patients progressed from having mild dysarthria to having anarthria in a mean time of 4.8 years. The most common symptoms at onset were speech problems and developmental delay.…”
mentioning
confidence: 98%